Analysis of The Quality Recycled Aluminum Mix of Soft Drink Cans And Engine Block With Sand Casting Method Volcanic Ash - Ivan Junaidi Abdul Karim; Kifli Umar; Sukiman Sukiman (ICETIA, 2016)
The use of aluminum for construction materials continues to rise, this led to use of aluminum raw materials continue to increase, and led to scarcity of raw material for aluminum. Recycles aluminum waste can reduce the use of aluminum raw materials. Recycled aluminum material like the soft drink cans have low mechanical properties, so that the necessary a mixture of aluminum with characteristics better mechanical properties to improve mechanical properties, one of which is waste engine block. Scrap mix soft drink 70% and 30% scrap engine block melted together. After melting do foundry in the mold of volcanic ash with water binding 10% in difference of pour temperature 660oC, 690oC and 720oC. Shaped silicon microstructure visible polygons or nearly unanimous well as large size and shape of the lines very little between the Al matrixes. Hardness increased at pouring temperature of 660oC is 32.2 HVN, and decreasing at pouring temperature of 720oC is 26.6 HVN. Tensile strength increased by 59.09 kg/mm2, at temperature 660oC pouring, and decreasing at pouring temperature of 720oC is 32.91 kg/mm2. Increased porosity in pouring temperature 660°C is 5.3%, and decreased in pouring temperature 720oC, is 3.9%.